The Influence Of Brand Image, Brand Satisfaction And Brand Trust On H&M Customer Brand Loyalty In The Jabodetabek Area - Muhammad Rakan Harids; Afif Zaerofi (Jurnal Ekonomi, 2024)
Fast fashion is a phenomenon in the clothing industry that offers the latest fashion trends at low prices and fast production times. one of the famous brands is H&M. In Indonesia, H&M has spread to 19 cities in the last 8 years.This study aims to analyze the effect of brand image brand satisfaction brand trust on H&M customer brand loyalty in the Jabodetabek area. Data collection was carried out by distributing online questionnaires via G-form. Multiple linear regression methods are used as data processing methods. The results of this study partially the Brand Image variable has no significant effect on brand loyalty, and the Brand Satisfaction variable, and Brand Trust have a significant positive effect on Brand Loyalty. Simultaneously all dependent variables affect the Brand Loyalty variable. In this study, all independent variables can influence the dependent variable by 58%.